If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(x+5)=3(2x+3)
We move all terms to the left:
7(x+5)-(3(2x+3))=0
We multiply parentheses
7x-(3(2x+3))+35=0
We calculate terms in parentheses: -(3(2x+3)), so:We get rid of parentheses
3(2x+3)
We multiply parentheses
6x+9
Back to the equation:
-(6x+9)
7x-6x-9+35=0
We add all the numbers together, and all the variables
x+26=0
We move all terms containing x to the left, all other terms to the right
x=-26
| 6x+14=51-7x | | p-70=-53 | | (5x+33)+(5x+2)=14x+3 | | x+(x+7)+(x-9)=1.48 | | 14-9x=32 | | 2u-54+u=180 | | (8x-10)(7x+1)=171 | | k+-40=16 | | (10+2x)(18+2x)-180=0 | | x2−7x−18=0 | | 2x-10-5x=20-5x | | (10+2x)(18+2x)-180=x | | x(5)=-125 | | 20-y=46 | | d-4=34 | | x2−7⋅x−18=0 | | 11+7x=10-3x-4x | | c-16=2c-72 | | 29=4+5c | | -3x-8=-6x+15 | | 1-6n-7n=-12 | | x5=-125 | | 8(k+5)=80 | | h+97=63 | | 4a+18=128 | | m+29/10=9 | | 120=15(c+2) | | 3x+8-5x=(16-6x)/2 | | (x+8)+(6x-5)+(2x-3)=180 | | 4/5-3/10x=1/10x-4/5 | | -3(n-3)=-36 | | x+11x=936 |